Pathogenic Bacteria, Pesticide Residues and Metal Content in Giant Fresh Water Prawn, Macrobrachium Rosenbergii (De Man) Sold in Local Markets (Journal of Bangladesh Academy of Sciences, 2011)
The giant fresh water prawn, Macrobrachium rosenbergii (de Man), a leading export item of Bangladesh was studied in terms of pathogenic bacteria, pesticide residues and metal contents. In microbiological analysis, total viable bacteria, total coliform, total faecal coliform, total Salmonella and total Vibrio count were ranged from 6.8 × 104 to 1.6 × 106, 1.5 × 102 to 1.8 × 105, 0.0 to 5.0 × 102, 0.0 to 1.8 × 102 and 0.0 to 3.6 × 102 cfu/gm, respectively. Pesticide residue was analyzed by HPLC. Out of six samples studied, one was found to be contaminated with Quinalphos and another with Cypermethrin, where the concentrations were 0.03 and 0.56 ppm, respectively, below the maximum residue limit set by joint FAO/WHO expert committee. Copper (Cu), cadmium (Cd) and lead (Pb) concentrations were measured by atomic absorption spectrophotometer. The range found for Cu and Cd was from 0.01 to 0.11 ppm and 0.01 to 0.06 ppm, respectively, which is below the maximum residue limit set by joint FAO/WHO expert committee (10 ppm for Cu and 0.2 ppm for Cd). Relatively high microbial load and presence of pathogens in all the tested samples, collected from local market revealed that the samples had exposure to an unhealthy environment.DOI: http://dx.doi.org/10.3329/jbas.v35i1.7974Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 91-97, 2011